ORGANIZATION OF BEACHES AND BATHS FOR CHILDREN AND THE WORK OF A SWIMMING INSTRUCTOR - Ashuraliev Alisher Bazarbaevich; Isakov Shukhratbek Muidinovich (International Engineering Journal For Research & Development, 2022)
The article reviews the work of the instructor in swimming and rescuing in waters in natural and artificial pools and - the organization of training those who are cannot swim and creation of conditions for safety forhaving classes and different exercises in water and gradual mastering the techniques of sports and applied swimming.